Propuesta de una metodología para la evaluación de las estructuras y determinación del tipo de mantenimiento de puentes colgantes en la región San Martín - Sanchez Viena, Zuleika Del Carmen (2015)
The present work of thesis to obtain the professional title of Civil Engineer, has been developed in order to make a scientific contribution to help solve problems of maintenance of bridges in the region San Martín, which when executed will provide a continuous, permanent and safe transport service, favoring a proper functioning of the system national roads of our country. The research is descriptive application at the basic level and has been conducted by the Faculty of Civil Engineering and architecture, Universidad Nacional de San Martín, developing the project at Campanilla district, province of Mariscal Cáceres in the Region San Martín. This work has been developed, making inspection detailed or qualified, assessment of the existing structure and the determination of the type of intervention of the Punta Arenas bridge, using the format of inspection by the Ministry's Transpo...